2021
DOI: 10.1108/jefas-10-2020-0328
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure, stock exchanges in Chile: 2007 to 2016

Abstract: PurposeThe article consists of analyzing the behavior of the determinants of the capital structure of Chilean companies between 2007 and 2016. The objective of this study was achieved through a typology of research based on bibliographic, documentary, exploratory and explanatory, considering annual financial reports from Economática in the chosen period.Design/methodology/approachAs this is a research study with a quantitative approach, the statistical tools used were descriptive analysis, Pearson correlation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
(69 reference statements)
2
2
0
1
Order By: Relevance
“…Besides, demand side factors such as PPETA (property, plant and equipment to total assets), LSL (log of sales), earnings before interest and tax to total assets (EBITA), market-to-book ratio (MTB), firm age, pay-out ratio and depreciation to total assets (DEPTA) consistently predict debt ratios in both the developed and developing countries. These outcomes align with the outcomes of Henrique et al . (2021) and Kumar et al .…”
Section: Discussion Of Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Besides, demand side factors such as PPETA (property, plant and equipment to total assets), LSL (log of sales), earnings before interest and tax to total assets (EBITA), market-to-book ratio (MTB), firm age, pay-out ratio and depreciation to total assets (DEPTA) consistently predict debt ratios in both the developed and developing countries. These outcomes align with the outcomes of Henrique et al . (2021) and Kumar et al .…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…In addition, due to favorable property rights (Claessens and Laeven, 2003) and better protection of creditors' rights (Giannetti, 2003), the collaterizability of intangible assets (goodwill assets) is more Besides, demand side factors such as PPETA (property, plant and equipment to total assets), LSL (log of sales), earnings before interest and tax to total assets (EBITA), market-to-book ratio (MTB), firm age, pay-out ratio and depreciation to total assets (DEPTA) consistently predict debt ratios in both the developed and developing countries. These outcomes align with the outcomes of Henrique et al (2021) and Kumar et al (2017) who reported EBITA, PPETA, LSL, firm age, MTB and DEPTA, as determinants of firms' debt ratios in developing and developed countries. The findings of Hang et al (2018), who found PPETA, MTB and EBITA as drivers of enterprises' debt ratios, are also supported by these data.…”
Section: Discussion Of Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Tejos & Pape Larre, 2021).Un estudio realizado en Chile por RabeloHenrique et al (2021) que analiza el comportamiento de los determinantes de la estructura de capital de una muestra de 240 empresas que cotizan en bolsa, concluye que la variable rentabilidad se orienta al enfoque de la Teoría del Orden Jerárquico, con una relación negativa respecto al endeudamiento; y que, las variables independientes liquidez, tangibilidad y rentabilidad tienen una influencia significativa sobre el endeudamiento.En el contexto de Ecuador, un estudio realizado por Espinoza et al (2024) sobre la estructura de financiamiento y la rentabilidad de las Pymes que cotizan en el mercado bursátil, utilizo un modelo de regresión cuantílica, en donde la variable dependiente es el retorno sobre activos y las variables independientes son tamaño y deuda. Los autores evidenciaron que la deuda y el tamaño se relación negativamente con el retorno sobre activos.…”
unclassified